Comparative Analysis on Text Watermarking Techniques: Literature Review - Abdulameer Naji , Ahmed; Shakir Baawi , Salwa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2023)
One of the common vast practices used for text authentication and ownership verification nowadays is through an information-hiding technique known as watermarking, which dates back to the 1990s. This paper investigates digital watermarking and its techniques that primarily focus on text watermarking. At the same time, it also tries to give a distinctive taxonomy in dealing with watermarking based on each technique. Two types of watermarking taxonomy were discussed, that includes of the type technique and attack. Techniques of text watermarking can then be further separated into three categories: embedding, approaches, and extraction. The approaches of text watermarking can be split into four categories: structure or format-based methods, text-image-based, zero-text watermarking, and linguistics ways. Ways belonging to each category were studied, and comparisons between each way are introduced by highlighting the findings. This paper also confirmed that there are principal requirements that require to be further explored and taken into account in the design of future watermarking systems, which are imperceptibility, capacity, security, and robustness.